QTL mapping for rust resistance in groundnut (Arachis hypogaea L.): QTL MAPPING FOR RUST RESISTANCE IN GROUNDNUT (ARACHIS HYPOGAEA L.) - ROHINI M KOLEKAR (Journal of Oilseeds Research, 2018)
Among biotic stress, rust is the major fungal disease of groundnut which causes drastic yield loss globally. Cultivation ofresistant genotype is better than the use of chemical fungicides for sustainable agriculture. Considering the limitations of traditional breeding method which rely on the phenotypic selection, Marker assisted breeding (MAB) is more advantageous for the development of resistant genotype. Many different types of molecular markers are being developed in the groundnut and also being used to map Quantitative trait loci (QTL) for rust resistance. Identification of molecular markers which are closely linked to the QTL and/or candidate gene for rust resistance and their utilization in the Marker assisted selection (MAS) has been noticed in this review. Breeders can implement those molecular markers for the screening and development of rust resistant genotypes in groundnut.